Plasma YKL-40 Elevation on Admission and Follow-Up Is Associated with Diastolic Dysfunction and Mortality in Patients with Acute Myocardial Infarction - Selcuk Pala; Munevver Sari; Gokhan Kahveci; Elnur Alizade; Ugur Arslantas; Abdulkadir Uslu (Cardiology Research and Practice)
Objective. The aim of the study was to determine an association between the plasma YKL-40 level and echocardiographic left ventricle systolic and diastolic function parameters in patients with acute myocardial infarction. Subjects and Methods. The study included 46 patients with acute myocardial infarction. Serum brain natriuretic protein (BNP) and YKL-40 levels were analyzed on admission and after one month. Left ventricle systolic and diastolic functions and Tei index were computed by transthoracic echocardiography. Results. Plasma YKL-40 was significantly higher in patients with acute myocardial infarction (AMI) (101.7 μg/L versus 34 μg/L, resp., p<0.001) and remained higher than in healthy subjects after one month. The levels of YKL-40 on admission were correlated with log BNP on admission (r=0.41,p=0.004), Tei index (r=0.44,p=0.002), left atrium volume index (r=0.32,p=0.02), and mitral septal annular E/e′ (r=0.44,p=0.003). Death was more frequently observed in patients with plasma YKL-40 above the median value than in those with plasma YKL-40 below the median value (p=0.001; OR = 13.6 (2.5–72.3)). Conclusion. YKL-40 elevations in patients with AMI remain at least one month and are associated with serum BNP elevations, diastolic dysfunction, and long-term increased overall mortality. It has prognostic importance in patients with AMI.